Ling-Li and the Phoenix fairy : a Chinese folktale - Greene, Ellin, 1927-; Wang, Zong-Zhou, 1946- (New York : Clarion Books, 1996)
Retells a Chinese tale in which a girl's colorful wedding jacket is stolen and torn into pieces, which ultimately become the flowers we know as impatiens.
"Retold from Folk tales from China (Foreign Languages Press, Peking)"--T.p. verso.
School Library Journal
Publisher's Weekly
Booklist
4.2
K-3
Keywords: Impatiens -- Folklore; Folklore -- China; Impatiens -- Folklore; Folklore -- China